The influence of being pregnant during the COVID-19 pandemic on birth expectations and antenatal bonding. (1st January 2023) - Schaal, Nora K.; Hagenbeck, Carsten; Helbig, Martina; Wulff, Verena; Märthesheimer, Sarah; Fehm, Tanja; Hepp, Philip
ABSTRACT: Purpose: The aim of the present study was to compare birth expectations and antenatal bonding of women pregnant prior to and during the COVID-19 pandemic. Materials and methods: In total, 74 pregnant women (mean age: 33.9 ± 4.1 years, gestational age: 36 ± 2 weeks) participated in the study, who were pregnant either during the the COVID-19 pandemic ( corona group, N = 35, April–July 2020) or before the pandemic ( control group, N = 39, October 2017–January 2019). Birth expectations were measured using the Wijma Delivery Expectancy Questionnaire (WDEQ) and Salmon's Item List (SIL) and antenatal bonding with the Maternal Antenatal Attachment Scale (MAAS). Additionally, the corona group indicated their level of worry regarding different pandemic-related aspects using visual analogue scales. Results: The corona group displayed significantly elevated fear of childbirth measured by the WDEQ and lower antenatal bonding quality compared to the control group . The additional items regarding COVID-19 burdens highlighted that the aspects that the partner may not be present during labour and that no visitors will be allowed in hospital were associated with the highest worries. Conclusions: Midwives and gynaecologists should be aware of the negative impact of the COVID-19 pandemic on fear of childbirth and antenatal bonding .